HOLOCENE FORAMINIFERAL FAUNA AT THE REGION OF PHAN VINH ISLAND, TRUONG SA ARCHIPELAGO AND SOME RELATED PROBLEMS - Ngoc, Nguyen (Vietnam Journal of Marine Science and Technology, 2018)
Holocene Foraminiferal fauna at the area of Phan Vinh island, Truong Sa archipelago is relatively abundant and diverse in both taxonomic composition and ecological characteristics. The initial research results have identified 69 species (excluding several ones unidentified) belonging to 42 genera, 25 families and 6 orders. Among them, the representatives of the genera of Calcarina, Amphistegina, Heterostegina, Elphidium, Amphisorus, Marginopora, Sorites, Parasorites, Peneroplis, Archaias, Siphonipheroides, Septotextularia are predominant. They characterized by the shallow, transparent and warm marine environments of the region of Truong Sa archipelago during Holocene. Some problems related to this fauna at the area of Phan Vinh island such as biodiversity of coral-reef ecosystems, stratigraphic and paleogeographical significances, and its role of reef - building are also mentioned in this article. In addition, for the modern Foraminifera in the world, today they are being used as ‘biomarkers’ (bioindicators) in assessing and monitoring environmental quality of coral reef ecosystems in particular and marine environment in general. In Vietnam, this method has not been applied, but in the future, this is one of the methods that should be concerned. In addition, in aquaculture the Foraminifera is also a source of nutrition that should not be ignored